2017
DOI: 10.1038/cddis.2017.421
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA XIST expedites metastasis and modulates epithelial–mesenchymal transition in colorectal cancer

Abstract: Tumor progression and metastasis is the main cause of death in colorectal cancer (CRC). Long noncoding RNAs (lncRNAs) are critical regulators in various diseases including human cancer. In this study, we found that lncRNA XIST was overexpressed in CRC cell lines and tissues. High expression of lncRNA XIST was associated with adverse overall survival in CRC patients. Knockdown of lncRNA XIST remarkably inhibited CRC cell proliferation, invasion, epithelial–mesenchymal transition (EMT) and CRC stem cell formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
146
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(154 citation statements)
references
References 36 publications
8
146
0
Order By: Relevance
“…Increasing studies revealed the oncogenic function of XIST in several tumors, such as gastric cancer [26], nasopharyngeal carcinoma [27], and hepatocellular carcinoma [28], through inducing cell proliferation, invasion and metastasis.. There have been documents reporting the carcinogenicity of XIST in CRC [10,11]. Moreover, a previous study demonstrated that XIST was significantly upregulated in 5FU-resistant CRC cells, and enforced expression of XIST inhibited 5FU-induced cell cytotoxicity in CRC cells [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing studies revealed the oncogenic function of XIST in several tumors, such as gastric cancer [26], nasopharyngeal carcinoma [27], and hepatocellular carcinoma [28], through inducing cell proliferation, invasion and metastasis.. There have been documents reporting the carcinogenicity of XIST in CRC [10,11]. Moreover, a previous study demonstrated that XIST was significantly upregulated in 5FU-resistant CRC cells, and enforced expression of XIST inhibited 5FU-induced cell cytotoxicity in CRC cells [12].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of XIST has been reported in the genesis and development of multiple neoplasms, highlighting its prognostic and clinicopathological value in cancers [9]. Recent studies have documented that XIST expression was significantly increased in CRC tissues and cells, and functioned as an oncogene in human CRC through facilitating cell proliferation, migration, invasion and EMT [10,11]. Moreover, it was also reported that XIST was significantly upregulated in 5-fluorouracil (5FU)-resistant CRC cells, and enhanced XIST restrained 5FU-induced cytotoxicity in CRC cells by promoting the expression of thymidylate synthase [12].…”
Section: Introductionmentioning
confidence: 99%
“…XIST has been demonstrated to play oncogenic function in multiple tumours. For example, XIST regulates colorectal cancer development and metastasis by the competition of miR‐200b‐3p to regulate ZEB1 expression . Meanwhile, XIST regulates the growth, invasion, and migration of bladder cancer by interacting with miR‐124 to target androgen receptor .…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of lncRNAs has been confirmed involved in initiation and progression in several cancers including CRC. Recently, more and more lncRNAs have been reported to play critical roles in CRC; however, the roles of lncRNAs in CRC are remaining poorly defined (Chen, Chen, et al, , Chen, Lu, et al, ; Li et al, ). Here, we found that SCARNA2 was obviously upregulated in CRC tissues compared with the ANTs.…”
Section: Discussionmentioning
confidence: 99%